Conservation of Transit Peptide-Independent Protein Import into the Mitochondrial and Hydrogenosomal Matrix - Garg, Sriram; Stölting, Jan; Zimorski, Verena; Rada, Petr; Tachezy, Jan; Martin, William F; Gould, Sven B (Genome biology and evolution, 2015)
The origin of protein import was a key step in the endosymbiotic acquisition of mitochondria. Though the main translocon of the mitochondrial outer membrane, TOM40, is ubiquitous among organelles of mitochondrial ancestry, the transit peptides, or N-terminal targeting sequences (NTSs), recognised by the TOM complex, are not. To better understand the nature of evolutionary conservation in mitochondrial protein import, we investigated the targeting behavior of Trichomonas vaginalis hydrogenosomal proteins in Saccharomyces cerevisiae and vice versa. Hydrogenosomes import yeast mitochondrial proteins even in the absence of their native NTSs, but do not import yeast cytosolic proteins. Conversely, yeast mitochondria import hydrogenosomal proteins with and without their short NTSs. Conservation of an NTS-independent mitochondrial import route from excavates to opisthokonts indicates its presence in the eukaryote common ancestor. Mitochondrial protein import is known to entail electrophoresis of positively charged NTSs across the electrochemical gradient of the inner mitochondrial membrane. Our present findings indicate that mitochondrial transit peptides, which readily arise from random sequences, were initially selected as a signal for charge-dependent protein targeting specifically to the mitochondrial matrix. Evolutionary loss of the electron transport chain in hydrogenosomes and mitosomes lifted the selective constraints that maintain positive charge in NTSs, allowing first the NTS charge, and subsequently the NTS itself, to be lost. This resulted in NTS-independent matrix targeting, which is conserved across the evolutionary divide separating trichomonads and yeast, and which we propose is the ancestral state of mitochondrial protein import.
Keywords: molekulární evoluce; Saccharomyces cerevisiae; mitochondrie; transport proteinů; proteiny - lokalizační signály; mitochondria; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; protein import; TOM/TIM; Trichomonas vaginalis; Protein Sorting Signals; Mitochondrial Proteins; mitosomes; Protein Transport; Mitochondria; hydrogenosomes; mitochondriální proteiny; Evolution, Molecular